Impact of metering of tube wells on groundwater use in West Bengal, India. - Meenakshi, J.V.; Banerji, A.; Mukherji, Aditi; Gupta, A. (International Water Management Institute, 2012)
In this Highlight, the impact of metering of electric tube wells on groundwater use in West Bengal, India was quantified. Quantification of impact was made feasible through surveys conducted in 2004 and 2007 and then again a follow-up survey in 2010 by revisiting the same villages and households. Difference in difference framework was used to quantify the impact. The major result is that the expected impact on reducing pumping hours was felt only in the boro season. There is also some evidence that this decrease was not confined to irrigation on own-farm, but that water sales and purchases were also adversely affected as a consequence. Yet the metering did not influence either cropping patterns, or the output of boro paddy. The latter could well be explained by over use of water among those who irrigate their own farms, so that reductions in water use do not translate into decreased output. These impacts have to be seen against the backdrop of an overall decline in pumping hours that was seen in both control and treatment groups, which may have served to swamp the impact of the metering.